2020
DOI: 10.1177/1971400920965970
|View full text |Cite
|
Sign up to set email alerts
|

The many faces of glioblastoma: Pictorial review of atypical imaging features

Abstract: Glioblastoma is an aggressive primary central nervous system tumour that usually has a poor prognosis. Generally, the typical imaging features are easily recognisable, but the behaviour of glioblastoma multiforme (GBM) can often be unusual. Several variations and heterogeneity in GBM appearance have been known to occur. In this pictorial essay, we present cases of pathologically confirmed GBM that illustrate unusual locations and atypical features on neuroimaging, and review the relevant literature. Even innoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…The diagnosis of polymer-associated DL is essentially a diagnosis of exclusion, and thus largely depends on clinicians being aware of this potential diagnosis and excluding differential diagnosis. 15 Symptom onset can vary (here 3–24 weeks from the preceding procedure) and present as focal neurologic deficits or seizure or, more unspecific, as headache and dizziness. The flow diverter device has been reported as being safe, 16 but a recent case series has described symptoms 4 years after flow diverter stenting of an internal carotid aneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of polymer-associated DL is essentially a diagnosis of exclusion, and thus largely depends on clinicians being aware of this potential diagnosis and excluding differential diagnosis. 15 Symptom onset can vary (here 3–24 weeks from the preceding procedure) and present as focal neurologic deficits or seizure or, more unspecific, as headache and dizziness. The flow diverter device has been reported as being safe, 16 but a recent case series has described symptoms 4 years after flow diverter stenting of an internal carotid aneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…Adding to these qualitative features, quantitative variation of tumour parts plays an important role: the percentage of the mesenchymal component has been reported to correlate with improved survival time. 12 , 33 The ratio of different components might also influence the radiological phenotype, and GBM can have atypical imaging features as well; 34 however, a correlation of the extent or the subtype of the mesenchymal part with imaging parameters has not been established. The broad spectrum of possible cell differentiation in combination with the close relationship to GBM might explain our difficulties in discriminating the imaging characteristics of GSC and GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its separation from the surrounding systems and the existence of the blood–brain barrier (BBB), which impedes the movement of many immune cells and chemotherapeutics, GBM imposes a big challenge for drug delivery [ 5 , 66 ]. Moreover, for drug development, the complex genetic and molecular environment of glioblastoma is an obstacle, which led to the lack of drug approval in the past decade.…”
Section: Future Therapeutics: From Understanding To Tacklingmentioning
confidence: 99%
“…Being a semi-solid and highly heterogeneous tumor, GBM has several unique physiochemical, mechanical, and biological features [ 3 , 4 ]. Recent studies showed that the extracellular matrix (ECM) of the brain and its alterations around the GBM tumor niche are directly linked to the rapid progression of GBM [ 4 , 5 ]. In fact, upon genetic mutation–driven GBM tumor formation, changes simultaneously occur in the TME, including in the ECM [ 6 ].…”
Section: Introduction: Glioblastomamentioning
confidence: 99%